Risk Factors for Type 2 Diabetes Mellitus in Women of Childbearing Age at Unaaha Public Health Center, Konawe Regency - Erwin Azizi Jayadipraja; Muh Natsir; Timbul Supodo; Komang Ayi Sukma (Public Health of Indonesia)
Introduction: The prevalence of DM at the Unaaha Health Center in 2017 was 1.12 per 1000 population, increased by 2018 to 2.4 per 1000 population and increased in 2019 by 4.6 per 1000 population. The purpose of this study was to determine the risk factors for the incidence of type 2 diabetes mellitus in women of childbearing age at the Unaaha Public Health Center.